Automated Black- and White-Box Testing of RESTful APIs With EvoMaster - Arcuri, Andrea (IEEE software, 2021)
We apply EvoMaster to eight representational state transfer application programming interfaces; show how the tool can be used to automatically generate test cases that can find several bugs, even when using a naive black-box approach; and discuss challenges that must be taken into account.